Trophoblast-Expression of Interleukin-6 (IL-6) and Human Chorionic Gonadotropin (hCG) inWomen with Recurrent Abortion ComparedWith Normal Pregnancy - Salman H. Amal; Al-Zubaidy A. Ghaith; Hussain A. Sulaf (College of Pharmacy / Mustansiriyah University, 2008)
Objective: We studied the estimation of IL-6 and hCG expression in immunohistochemistry in women with unexplained Recurrent Spontaneous Abortion (RSA) and find out whether or not IL-6 regulates human Chorionic Gonadotropin release (hCG). An immunohistochemistry technique was performed to detect and determine the immunohistochemistry expression of IL-6 and hCG proteins using paraffin embedded sections of curettage samples obtained from 50 women, who were divided into three groups: 25 women with RSA, 15 women with abortion for the first time, and 10 women with induced abortion. The levels of the immunohistochemistry expression of both IL-6 and hCG were found to be highly significant increased in group 3 as compared with group 1 and group 2 (P<0.001), with a significant positive correlation between these two parameters (P<0.05) in three groups. The trophoblasts expression of IL-6 might play a role in stimulation of the expression of hCG during pregnancy.